Inequity in dental care utilisation: what gets delivered gets known - evidence from Chandigarh and Haryana - Bhatnagar, Nidhi; Mohindroo, Atysha; Verma, Himbala; Aggarwal, Arun Kumar (International Journal Of Community Medicine And Public Health, 2017)
Background:Studies till date have focussed on the prevalence of dental disorders and the related health seeking behaviour. Inequity in seeking dental health care is debated based on age, wealth and education. This study focussed on geographical inequity in awareness and treatment seeking for dental health care. Methods:Paper compares awareness for dental problems and related treatment practices of rural population of a district in Haryana with rural area of adjoining union territory Chandigarh. Results:In rural Chandigarh, more than 90% knew about dental caries and dentures, whereas, in rural Haryana only 50% knew about dental caries and 70% about dentures. Knowledge about gum problems, mal-alignment, and growth of plaque was low. Knowledge about scaling, and root canal treatment was low in both rural areas. Majority of subjects (66.7%) attending health camp in rural Haryana never underwent a dental check-up, compared to 41% in rural Chandigarh. In rural Haryana, commonly available dental services are extractions and filling, whereas, Chandigarh has wider spectrum of services available. Conclusions:Poor awareness of dental morbidity, treatment practices and treatment seeking is possibly linked to the availability of the services. Overall, penetration of newer treatments for dental health care in the community has been slower and more so in the rural areas.